Premature Ovarian Insufficiency, an important cause of early menopause: Review of the literature with clinical case reports - E.P. Robles Granda; F.N. Briones Moreira (ESPOCH Congresses, 2023)
Abstract Early menopause is established by the definitive cessation of menstrual cycles and marks the end of the reproductive stage of women before the age of 40. This condition can be caused by premature ovarian insufficiency (POI) of spontaneous development or external causes, which impairs the reproductive capacity of young women and their quality of life, with medium and long-term consequences such as genitourinary dysfunction, dyslipidemia, insulin resistance, decreased bone mineral density, cardiovascular, cognitive alterations, among others. Its prevalence is around 1% in those under 40 years of age, and the objective of this work is to review important aspects of premature ovarian insufficiency and its relationship with the development of menopause, objectified through the report of 2 significant clinical cases. Case 1: A 26-year-old patient, nulliparous, with amenorrhea from the age of 22 to the current date, with values of FSH and LH, Estradiol, and anti-Müllerian Hormone, compatible with menopause. Case 2: A 30-year-old patient, nulliparous, who at the age of 16 underwent right oophorectomy for immature cystic teratoma, with 6 months of amenorrhea and FSH, LH, Estradiol, and anti-Müllerian hormone values compatible with menopause. Both patients suffered from menstrual irregularities since their menarche, which was evaluated by specialists when the periods of amenorrhea were extensive. This underscores the importance of a timely evaluation of IOP in young people who persist with menstrual disorders after 2 years of menarche, with diagnostic studies and management that help preserve their reproductive health to which they are entitled.